Accumulation of arsenic by aquatic plants - Lee, C.K.; Low, K.S.; Hew, N.S. (Elsevier Science, 1991)
Ten varieties of aquatic plants were collected from 22 pools resulting from tin-mining activities in and around Kuala Lumpur. The concentrations of arsenic in these plants partially reflected the concentrations of arsenic in pool water, which ranged from 0.002 to 0.25 μg ml-1. Uptake of arsenic by one of the aquatic plants, hydrilla, Hydrilla verticillata Casp., was studied in the laboratory. Results indicated that uptake was a function of initial arsenic concentration. In the presence of high phosphate concentrations, uptake of arsenic by Hydrilla verticillata was inhibited. Hydrilla verticillata can be used as a bioindicator of arsenic pollution in the aqueous ecosystem as it fulfilled the criteria for an indicator organism.